Kelas Sinema: Community-Based Documentary Film Production Training as an Effort to Preserve Tengger Cultural Heritage - Ardiansah Putra Perdana; Hari Windu Asrini (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
The rapid growth of tourism in the Bromo Tengger Semeru National Park (TNBTS) has created new economic opportunities for the Tengger community while simultaneously posing challenges to the preservation of local cultural values. One of the major issues is the limited capacity of local youth to document and communicate their own cultural narratives through audiovisual media. This community service program addressed this issue by implementing Kelas Sinema, a community-based documentary filmmaking training program in collaboration with Lingkaran Space and Shelter Kopi Bromo in Sukapura, Probolinggo. The program employed the Asset-Based Community Development (ABCD) approach integrated with the Participatory Video (PV) method to strengthen local capacities through participatory learning. The activities consisted of community asset identification, documentary filmmaking training, interactive discussions, practical audiovisual exercises, and program evaluation. The training introduced participants to visual language, documentary storytelling, cinematography, and community-based cultural documentation. The results indicate that participants demonstrated increased knowledge and skills in documentary film production, stronger awareness of the importance of preserving Tengger culture through audiovisual media, and active engagement throughout the learning process. The program also fostered collaboration among local communities and strengthened the role of documentary filmmaking as a medium for cultural education, community participation, and sustainable cultural preservation in the TNBTS area.